Phytochemical Screening and Biological Activities of Oxalis corniculata Leaves of Sindhupalchowk District, Nepal - Pandey, Kamala; Pokhrel, Shanta (BIBECHANA, 2022)
The Oxalis corniculata (Oxalidaceae) is one of the most potential medicinal herbs and well known for multiple therapeutic properties (anti-inflammatory, anticancer, antioxidant, antimicrobial, analgesic and diuretic activity). This study investigated phytoconstituents, antibacterial activity and antioxidant activity of Oxalis corniculata leaves extract. Methanol based phytochemical screening of Oxalis corniculata revealed the presence of alkaloids, proteins, phenols, flavonoids, glycosides. The antibacterial activity revealed better potential inhibitory effect against gram-negative bacteria, particularly Escherichia coli and Salmonella typhi compared to Staphylococcus aureus, a gram-positive bacterium. However, 1% methanol extract showed highest antibacterial activity against Escherichia coli followed by Staphylococcus aureus and Salmonella typhi. Antioxidant activity of the methanol extract with 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging showed antioxidant activities with 3.87 µg/mL IC50 value.BIBECHANA 19 (2022) 27-33